LAYANAN KESEHATAN REPRODUKSI REMAJA DALAM UPAYA PENCEGAHAN ANEMIA PADA REMAJA DI KABUPATEN PEKALONGAN - Wahyu Ersila; Lia Dwi Prafitri (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Young women are more susceptible to anemia than boys. That's because the iron requirement in young women is 3 times greater than in men. Young women every month have menstruation that automaticallybleeds. That is why young women need iron to restore their body condition to its original state. It is unfortunate that most teenage girls do not realize it because of too much teenage activity, or a restricted diet because they want to look slim and so on. Community service activities aims to help improve adolescent  knowledge about anemia in adolescents and prevent the occurrence of anemia in adolescents. Activity targets are young women aged 12-15 years who are in MTS Yapik Karanganyar Pekalongan district. The expectedbenefits of this activity is the increased knowledge of adolescents about the importance of reproductive health in this case to prevent the occurrence of anemia with the extension services anemia, held a discussionon anemia and drinking iron tablet together to provide awareness among adolescents about the importance of preventing anemia in adolescents. The methods used in this activity are discussion of questions and answers, lectures, and demonstrations. Resource persons in this activity is a lecturer team STIKESMuhammadiyah Pekajangan, teacher Yapik MTS. The results of this activity are almost all teenagers active in the activity and an increased knowledge about anemia in adolescents.Keywords: Anemia, adolescents, iron tablets